PLACENTAL SITE NODULE : A RARE CASE REPORT - Nurxhan Ajeti; Arta Islami Zulfiu; Ana Kocevska; Ilirjan Zulfiu (Македонско лекарско друштво = Macedonian medical association, 2025)
Placental site nodule is a rare, benign non neoplastic lesion of intermediate trophoblastic origin which is thought to represent incomplete involution of the placental implantation site. It is often discovered incidentally in women in reproductive period during evaluation for abnormal uterine bleeding. Although typically not harmful, they can sometimes mimic more serious condition, requiring careful diagnosis.It can be associated with recurrent pregnancy loss , infertility, history of prior intrauterine instrumentation and chronic endometritis. We present a case, 30- year old women who developed abnormal uterine bleeding one year after a full term vaginal delivery. From obstetric history,one pregnancy ended with vaginal delivery of the fetus in term without complication.She had no other interventions on the uterus.Transvaginal ultrasound revealed an intrauterine lesion suspected to be an endometrial polyp. A diagnostic endometrial curettage was performed to evaluate for the endometrial pathology. The obtained tisssue was sent for histopathology analysis . According to the described morphology and immunohistochemical analysis during the histopathological examination of the endometrial tissue, finding corresponds to a placental site noule : a small 4 mm nodule composed of intermediate trophoblastic cells of chorionic type embedded in markedly hyalinized stroma. The trophoblastic cells very in size, from relatively small with uniform nuclei to cells with abundant eosinophilic to ampholphilic cytoplasm (PLAP +,BHCG-). At the next check-up immediately after curettage, the endometrium was 10 mm , without pathological lesions intracavitary. Serum B - human chorionic gonadotropin was negative. On follow - up, the patient had regular menstruation and serum B-human chorionic gonadotrpin was negative. Placental site nodule should be considered in the differential diagnosis of intrauterine lesions, especially in women with recent pregnancy history .Timely and accurate diagnosis is essential to distinguish Placental Site nodule from malignant conditions,avoiding unnecessary interventions. Appropriate clinical management ensures optimal outcomes and reduces the risk of complication or misdiagnosis. Early recognition and follow - up are the key to minimizing long term consequences for women's reproductive health.
Keywords: placental site nodule; abnormal uterine bleeding; curettage; histopathology